Syndrome and Phenomenon of Wolff - Parkinson - White in Children (Literature Review) - N.V. Nagornaya; Ye.V. Pshenichnaya; S.A. Parshin (Zaslavsky O.Yu., 2013)
The article deals with the data on the history of the discovery and study of the phenomenon and syndrome Wolff - Parkinson - White (WPW). The features of the anatomy and electrophysiology of additional ways, mechanisms of attacks of atrioventricular reentrant tachycardia in WPW syndrome are considered. The role of the standard ECG, methods for topical analysis of additional atrioventricular connections and non-invasive electrophysiological studies in the diagnosis of this disease is shown.